2000
DOI: 10.1116/1.591179
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of WF6/N2/H2 plasma enhanced chemical vapor deposited WxN films as barriers for Cu metallization

Abstract: Low temperature plasma-assisted chemical vapor deposition of tantalum nitride from tantalum pentabromide for copper metallization W x N is a promising candidate as a barrier material for Cu metallization. In this work, we report the characterization of W x N films deposited by plasma enhanced chemical vapor deposition using WF 6 /N 2 /H 2 gas mixtures. The films are analyzed by Rutherford backscattering spectrometry, Auger electron spectroscopy, atomic force microscopy, x-ray diffraction, transmission electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…The resistivity of the WN film is insensitive to the N content if it is amorphous, but the resistivity increases drastically with the N content when it is in crystal form. 19 However, the WN films in Fig. 2c, either as-deposited or after annealing, were polycrystalline and their resistivities were dependent on the N concentration in the film.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The resistivity of the WN film is insensitive to the N content if it is amorphous, but the resistivity increases drastically with the N content when it is in crystal form. 19 However, the WN films in Fig. 2c, either as-deposited or after annealing, were polycrystalline and their resistivities were dependent on the N concentration in the film.…”
Section: Resultsmentioning
confidence: 98%
“…16 It was also reported that WN could be deposited as an amorphous-like film by plasma-enhanced chemical vapor deposition ͑PECVD͒ if an appropriate W/N ratio was obtained, i.e., 2-19. 19 However, in this study, the as-deposited WN film has a cubic crystal structure, as shown in the inset of Fig. 2c.…”
Section: G644mentioning
confidence: 96%
“…This indicates that the film has an amorphous structure both as deposited or post 700°C annealed. 2,29 This suggests that the film formation mechanism of ALD is different from that of CVD. 16 The spectra from other annealing temperatures, 400-600°C, have identical XRD spectra.…”
Section: A Structural Characterization By Xrd and Temmentioning
confidence: 99%
“…Tungsten nitride films have been proposed to be a good barrier layer to prevent inter-diffusion of Al or Cu and Si during subsequent high-temperature annealing processes. [1][2][3][4] Alternatively, chemical nitridation of tungsten metal and reduction of WCl 6 , WF 6 , and WO 3 by NH 3 at high temperatures have been employed. [5][6] Unlike many other transition metal nitrides, thin films of tungsten nitride are rarely grown by metal-organic chemical vapor deposition (MOCVD).…”
Section: Introductionmentioning
confidence: 99%